Analysis of scientific production of IoE big data research - Kaur, J.; Wongthongtham, Pornpit; Abu-Salih, B.; Fathy, S. (2018)
© 2018 IEEE. The investment on Internet of Everything is increasing exponentially. This new global technological approach opens the doors for connecting everything and anything. Such massive propagation of Big Data generated from a wide variety of sensors requires consolidated efforts to put forward solutions to address specific related business problems and needs. The aim of this paper is to provide a systematic review of the state-of-the-art scientific research on the Internet of Everything and Big Data. Top 20 journals are selected in this study comprising 112 articles in the domain. The paper discusses the results of affiliation analysis, keyword statistics, source statistics, citation analysis and co-citation analysis. The conclusion of this literature review suggests future opportunities and research directions in the era of Internet of Everything and Big Data.